KLASIFIKASI TINGKAT KEKERINGAN PADA DAERAH ALIRAN SUNGAI (DAS) LIMBOTO (Classification Of Drought Level In Limboto Watershed) - Sri Rahayu Ayuba; Munajat Nursaputra; Tisen Tisen (Universitas Muhammadiyah Gorontalo, 2018)
Abstract - Changes in land use are the socio-economic forces that most encourage changes and ecosystem degradation. Disruption of the hydrological cycle has caused